PENANGANAN TINDAK PIDANA KETENAGAKERJAAN BERDASARKAN PENDEKATAN KEADILAN RESTORATIF OLEH POLISI NEGARA REPUBLIK INDONESIA - Muhammad Rizky Febrianto Nasri; Yohana Apriliani Christianta Silaen; Xavier Nugraha (CV Rewang Rencang, 2023)
In handling criminal acts, the Police have begun to use a restorative justice approach based on Perpol 8/2021, but there is legal ambiguity regarding whether or not labor crimes can be resolved based on Perpol 8/2021. The problem formulation in this article is 1. What are the characteristics of handling labor crimes? 2. Does the police's handling of labor crimes based on a restorative justice approach conflict with Perpol 8/2021? The results of this research are that employment crimes can be resolved by the police based on a restorative justice approach, because they do not conflict with Perpol 8/2021.